Crustal shortening estimates across the north Indian continental margin, Ladakh, NW India - Corfield, R; Searle, M (2000)
A structural and lithological map has been produced covering the Spontang ophiolite and the north Indian continental margin from the Indus Suture Zone in the north to the high-grade metamorphic rocks and granites of the High Himalaya in the south. Cross-section balancing techniques have been used to identify, quantify and sequentially restore three major phases of deformation (D1-3) affecting the north Indian continental margin resulting in >85 km (280%) shortening. D1 in the late Cretaceous involved obduction of the Spontang ophiolite, associated Neo-Tethyan thrust sheets and Mesozoic continental slope deposits onto the outer passive margin. D1 was responsible for 200% shortening by internal folding and duplex formation within stratigraphic units in the outer shelf, but did not affect the innermost parts of the Indian passive margin. Restoration of later structures suggests that the allochthonous thrust sheets were emplaced a minimum of 70 km onto the continental margin. D2 from the early Eocene to Oligocene was the main phase of deformation associated with the collision of India and Asia. Re-thrusting places the Spontang ophiolite and associated melanges over the Maastrichtian to Lower Eocene neo-autochthonous cover which accommodated 140-160% shortening in the hanging wall. D2 progressed with the propagation of thrusting down section and towards the foreland causing crustal thickening and Barrovian metamorphism. The thick, argillaceous late Cretaceous Kangi La Formation decoupled deformation in higher and lower structural levels in outer shelf areas. D3 backthrusting and break-backthrusting in the late Tertiary formed a pop-up structure at the northern edge of the continental margin associated with a further 190-230% shortening and inversion of structures in the Indus Suture Zone. A major anticlinal structure also initiated across the southern edge of the Indus Suture Zone. South of Spontang reactivation of D2 thrusts as late D2/D3 normal faults was associated with gravitational collapse of the High Himalaya to the south. Extensional movement on these structures was probably concomitant with shortening in the pop-up structure to the north. A reduction in present day and restored thickness of the Tethyan Himalaya and an increase in absolute shortening from east to west probably reflects a variation in the partitioning of deformation across the whole width of the orogen. This may be associated with the indentation of India into Asia to the northwest.